PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN INDEKS INFOBANK15 PERIODE 2017-2021 - Sholeh Nur Rohmat; Kholifatus Shaniyah (Journal of Management and Social Sciences, 2022)
This study intends to identify the influence of the Independent Board of Commissioners and the Audit Committee on Company Value. The company sample uses the InfoBank15 Index company with an observation period from 2017 to 2021, a total of 6 companies. The secondary database used was obtained from the Indonesia Stock Exchange and the company's official website. The method of data analysis is in the form of multiple linear regression using the IBM SPSS model 26 analysis tool. The results show that partially the Independent Board of Commissioners and the Audit Committee have no influence on Company Value. Simultaneously the Board of Independent Commissioners and the Audit Committee are also unable to influence the InfoBank Index Corporate Value15.